2021
DOI: 10.1021/acsabm.1c00285
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Carbon Monoxide Prodrug-Loaded Nanoplatforms for Effective Photoacoustic Imaging-Guided Photothermal/Gas Synergistic Therapy

Abstract: Multifunctional cancer treatments based on gas therapy combined with other cancer treatments have gained tremendous attention and hold great promise in biomedical applications. In this study, a carbon monoxide-releasing nanoplatform combined with near-infrared (NIR) laser-triggered photothermal therapy (PTT) was constructed. The nanoplatform was composed of manganese pentacarbonyl bromide (MnCO)-loaded g-carbon nitride/polypyrrole (CNPpy) nanomaterials (MnCO@ CNPpy). MnCO can be triggered to produce CO under H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Recently, the effectiveness of gas-based therapy has been increased using other therapeutic approaches, including chemotherapy, radiation therapy (RT), photodynamic therapy (PDT), ultrasound therapy (US), photothermal therapy (PTT), and starvation therapy. 1,4,39–42 Among these therapeutic modalities, PTT has garnered significant attention due to its excellent precision in remote spatiotemporal control and its non-invasive therapeutic attributes. 43–45 It's worth noting that PTT utilizes light-absorbing agents to transform light energy into heat, which is then utilized for cellular thermal ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effectiveness of gas-based therapy has been increased using other therapeutic approaches, including chemotherapy, radiation therapy (RT), photodynamic therapy (PDT), ultrasound therapy (US), photothermal therapy (PTT), and starvation therapy. 1,4,39–42 Among these therapeutic modalities, PTT has garnered significant attention due to its excellent precision in remote spatiotemporal control and its non-invasive therapeutic attributes. 43–45 It's worth noting that PTT utilizes light-absorbing agents to transform light energy into heat, which is then utilized for cellular thermal ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Various stimuli-responsive CORMs have been developed, which can be triggered by endogenous stimuli or external factors such as light irradiation. Endogenous stimuli responsive CORMs always suffer from uncontrollable release of CO [18][19][20]. In contrast, light-triggered CO release from a photo-activated CORM (photoCORMs) has demonstrated appealing profile, which facilitates a precise spatial and temporal control over the CO liberation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that DNA-functionalized AuNPs (DNA-AuNPs) have high biocompatibility and stability, and the DNA-AuNP system can be used to construct nanomachines for biomedical applications. DNA can undergo conformational changes under different conditions, such as pH and temperature. Thus, DNA sequences induce structural changes in nanomachines. The self-assembly of DNA-functionalized AuNPs has been reported for in vitro diagnostics, and because of the unique molecular recognition ability of DNA molecules and the specific binding between single strands, the interaction between strands of complementary single-stranded DNA can be used to form ordered self-assemblies of originally disordered AuNPs, thus enhancing the photothermal effects. The commonly used stimulation methods include temperature, light, , pH, and redox. , By modulating the molecular design, a certain molecule with sensitive responsiveness to tumor markers is selectively introduced into AuNPs to prepare AuNPs with stimulation responsiveness to aggregate and to produce a photothermal effect at tumor sites. In recent years, researchers have designed ATP-responsive nanodrug delivery systems that take advantage of the differences in ATP inside (1–10 mM) and outside (<0.4 mM) tumor cells. , The increased glycolysis in malignant tumor cells resulted in significantly higher ATP levels than in normal cells, but few studies have focused on the ATP-induced aggregation of AuNPs in tumors to produce photothermal effects.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used stimulation methods include temperature, light, 50,51 pH, 46 and redox. 45,52 By modulating the molecular design, a certain molecule with sensitive responsiveness to tumor markers is selectively introduced into AuNPs to prepare AuNPs with stimulation responsiveness to aggregate and to produce a photothermal effect at tumor sites. In recent years, researchers have designed ATP-responsive nanodrug delivery systems that take advantage of the differences in ATP inside (1−10 mM) and outside (<0.4 mM) tumor cells.…”
Section: ■ Introductionmentioning
confidence: 99%